Deficit irrigation scheduling in processing tomato - Gatta G.; Giuliani M.M.; Monteleone M.; Nardella E.; De Caro A. (Water saving in Mediterranean agriculture and future research needs [Vol. 1], 2007)
In order to save water, a reduced crop irrigation regime is to be undertaken and the scheduling of irrigation becomes a crucial facet of the overall irrigation technique. Deficit irrigation can be applied regularly along the whole cropping season or according to the crop sensitivity to water with respect to different crop stages. In this latter case a 'regulated' deficit irrigation is carried out, converging watering in the most sensitive stages so to optimize crop productivity. Crop yield response to water can be synthetically stated by means of the ky coefficient (FAO, 1979), defined as the relative reduction in crop yield corresponding to a relative crop evapotranspiration deficit. Tomato, according to the FAO classification, is considered a moderately sensitive crop and its ky value is estimated equal to 1.05 over the total cropping season. Trials worked out from different authors in the same Mediterranean conditions, generally exhibited contrasting ky values, lower or higher than FAO, without discriminating from the different crop phenological stages. The aim of the paper, after two years of experimental trial, is to derive tomato ky values with respect to the whole crop cycle as well as to different crop stages. Interesting considerations are suggested as regard to tomato irrigation strategy.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)